1979
DOI: 10.1002/anie.197905991
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Structure Formation in Protein Gels

Abstract: The present article is concerned with the practical and theoretical aspects of gelation in protein systems. The processes involved are, inter alia, so complicated that several types of protein molecule assemblies and conformational changes during the association have to be considered. The gel network can be stabilized by five types of interaction: covalent crosslinking, polar interactions, hydrogen bonding, salt bridges and hydrophobic interactions. The microstructures of gels formed from fibrillated proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Much work has been done on the study of gel formation of biopolymers [7][8][9][10][11][12][13][14][15][16][17][18]. The biocompatibility and biodegradability of natural polymers like proteins, polysaccharides and nucleic acids, make them ideal for in vivo applications as compared to synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been done on the study of gel formation of biopolymers [7][8][9][10][11][12][13][14][15][16][17][18]. The biocompatibility and biodegradability of natural polymers like proteins, polysaccharides and nucleic acids, make them ideal for in vivo applications as compared to synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…EGG WHITE (EW) and ovalbumin (OV) aggregate to construct a three-dimensional gel network after denaturation with heat (Bezrukov, 1979;Johnson and Zabik, 1981;Ma and Holme, 1982;Kato and Takagi, 1987;Koseki et al, 1989;Kato et al, 1990). The egg protein gel structures can be stabilized by covalent disulfide cross-links and several secondary bonding forces, e.g., polar interaction, hydrogen bonding, and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The egg protein gel structures can be stabilized by covalent disulfide cross-links and several secondary bonding forces, e.g., polar interaction, hydrogen bonding, and hydrophobic interactions. The disulfide cross-links were strongly related to gel strength (Margoshes, 1990) and play an essential role in egg protein gelation (Bezrukov, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Tombs (1970) suggested that protein gelation could be considered in terms of statistical theories developed by Flory (1942) for synthetic polymers. However, Bezrukov (1979) reported that statistical aggregation is unlikely to occur because protein globules have a surface mosaic structure with sites differing in charge, density and sign, degree of hydrophobicity and the presence of disulphide groups. The present work indicates that the reactions took place in an orderly sequence until heating was stopped, thus resulting in reproducible gels provided that the protein concentration and time and temperature of heating were carefully controlled.…”
Section: Discussionmentioning
confidence: 99%